MediaPipe-LSTM: Multi-Task Pose Recognition for Safety and Creative Quality Control - Divian Nathaniel, Raymond (Journal of Computer Science and Research (JoCoSiR), 2025)
Spinal Muscular Atrophy (SMA) remains a critical genetic disease requiring early detection, yet conventional methods like PCR and genetic sequencing suffer from high costs, extended processing times, and limited accuracy in detecting minor mutations. This study addresses these challenges by developing an innovative integrated system that combines CRISPR-Cas biotechnology with artificial intelligence to revolutionize genetic disease detection. The research employs CRISPR system remodeling to optimize guide RNA design targeting SMN1 and SMN2 genes, integrated with a hybrid deep learning model combining Convolutional Neural Network and XGBoost for intelligent mutation prediction. Unlike traditional approaches, this system achieves detection accuracy exceeding 96.5% while significantly reducing processing time through automated AI-driven interpretation of CRISPR signals. The integration enables real-time analysis of complex genetic patterns, minimizes false detection rates, and generates precision-based therapy recommendations tailored to individual mutation profiles. This breakthrough offers substantial advantages over existing methods by providing faster, more accurate, and cost-effective genetic screening suitable for neonatal programs, particularly in resource-limited settings. The system demonstrates strong potential for clinical implementation, supporting early intervention strategies that can dramatically improve patient outcomes. By bridging molecular biology and computational intelligence, this research contributes a transformative framework for genetic disease detection that is scalable, efficient, and clinically applicable, paving the way for personalized medicine approaches in managing hereditary disorders.